2021
DOI: 10.1371/journal.pone.0259287
|View full text |Cite
|
Sign up to set email alerts
|

Investigating whether serum IGF-1 and IGFBP-3 levels reflect the height outcome in prepubertal children upon rhGH therapy: LG growth study database

Abstract: Serum insulin-like growth factor-1 (IGF-I) and IGF binding protein-3 (IGFBP-3) levels can be used to monitor the safety of recombinant human growth hormone (rhGH) therapy. In this study, we evaluated the changes in serum IGF-I and IGFBP-3 levels during rhGH therapy as a marker of height outcome in prepubertal children. Totally, 705 prepubertal children with short stature were enrolled from the LG Growth Study Database. Data for three groups of subjects were obtained as follows: Idiopathic GH deficiency (IGHD; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…These factors cast doubt on the use of IGFBP-3 as a diagnostic tool in evaluating the efficacy of GH therapy. Despite these disadvantages, some researchers have reported that changes in IGFBP-3 in children receiving GH therapy are significantly associated with growth response and have even suggested that IGFBP-3 may be a more useful marker than delta IGF-1 in predicting growth response (27). In the present study, we found that the increase in growth velocity in the first year in cases of GHD started on GH therapy was associated with increased IGFBP-3 levels.…”
Section: Discussionsupporting
confidence: 39%
See 1 more Smart Citation
“…These factors cast doubt on the use of IGFBP-3 as a diagnostic tool in evaluating the efficacy of GH therapy. Despite these disadvantages, some researchers have reported that changes in IGFBP-3 in children receiving GH therapy are significantly associated with growth response and have even suggested that IGFBP-3 may be a more useful marker than delta IGF-1 in predicting growth response (27). In the present study, we found that the increase in growth velocity in the first year in cases of GHD started on GH therapy was associated with increased IGFBP-3 levels.…”
Section: Discussionsupporting
confidence: 39%
“…On the other hand, Cutfield et al (26) determined that patients with GHD with low IGF-1 levels before GH therapy exhibited better growth responses in the first year of treatment. Kim et al (27) showed that serum Δ IGF-I levels measured in the first year of treatment in prepubertal cases with GHD started on GH therapy and for whom GH treatment was initiated can be used as a marker to predict the growth response. However, there are also opposing views.…”
Section: Discussionmentioning
confidence: 99%
“…Growth response in the first year of rhGH therapy is one of the best indicators of long-term height gain [ 24 ]. By applying Bang criterion to our study, the majority of cases (75%) were poor responders [14 cases (66.7%) IGHD, 6 cases (75%) ISS, and 10 cases (91%) SGA] .…”
Section: Discussionmentioning
confidence: 99%
“…Short stature is one of a growth and development disorder in children. Children with this disease have a signi cantly short stature for their age and gender and a deteriorated growth velocity, which seriously affect the physical and mental health of children and increase the family burden in varying degrees (10)(11)(12). Several factors, such as growth hormone de ciency, gene mutation, growth hormone resistance, and decreased growth hormone activity contribute to the development of short stature (13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%